Об эффекте зависания мелкой частицы переменной массы в воздушной среде - Ольшанский, Станислав Васильевич (НТУ "ХПИ", 2009)
Описано рух сферичної частки, що зменшує радіус за показниковим законом, нелінійним диференціальним рівнянням зі змінними коефіцієнтами. За допомогою спеціального перетворення знайдено аналітичний розв’язок задачі Коші в функціях Бесселя. Встановлено ефект зависання дрібної частки змінної маси в повітряному шарі обмеженої товщини.

The motion of a spherical particle is described which reduces radius under the exponential law, nonlinear differential equation with variable factors. Through special transformation the analytical solution of a Cauchy problem in Bessel functions is found. The fact of hover of a fine particle of variable mass in air environment under condition of infinite existence in time is established.
Keywords: газовая среда; легкие частицы; встречный поток; эффект отражения